Functional specialisation in EU value chains: Methods for identifying EU countries' roles in international production networks - Aleksandra Kordalska; Magdalena Olczyk; Roman Stöllinger; Zuzana Zavarska (The Vienna Institute for International Economic Studies (wiiw), 2022)
Geographically dispersed production networks have allowed countries to specialise in different functions of the value chain. By making use of two methodologies for quantifying the magnitude of functional specialisation - one based on trade flows and one based on FDI flows - detailed profiles of the functional specialisations of EU member states are identified. The analyses are conducted at the country, industry and regional level. In line with the existing literature, they reveal that EU-CEE countries are predominantly specialised in the fabrication stage, that is, they serve as 'factory economies', while the Western EU countries are mainly performing knowledge-intensive pre-fabrication activities - a characteristic of 'headquarter economies'. This dualism within the EU is confirmed by a cluster analysis. While functional specialisation patterns tend to be persistent, especially in the fabrication stage, there are also some signs of functional diversification in EU-CEE countries in more recent years. Still, these functional changes remain limited to a few industries. The dichotomy of factory and headquarter economies is also clearly discernible at the regional level. However, the fact that in most EU countries - mainly in the capital regions - there are some headquarter-type regions implies that a complete functional 'lock-in' in fabrication is less likely than suggested by the country-level patterns. Hence, while the results point towards major difficulties of functional diversification beyond the fabrication stage in the EU-CEE countries and regions, there are also several promising elements and trends discernible, in particular at the industry and the regional level.
Keywords: F15; F21; F23; F60; 330; functional specialisation; global value chains; smile curve; factory economy; greenfield FDI